Republic of Fiji - Poverty Trends, Profiles and Small Area Estimation (Poverty Maps) in Republic of Fiji (2003-2009) - World Bank (World Bank, 2012)
This report presents a detailed analysis of household poverty and its drivers - family, labor and human capital outcomes, social assistance transfers, and geography - based on new expenditure based poverty measures. The report is the culmination of a comprehensive year-long Aus AID funded collaboration between the Fiji Islands Bureau of Statistics (FIBOS) and the World Bank to develop new poverty measures and maps that produce poverty estimates at highly disaggregated levels. The report draws on the last two rounds of Household Income and Expenditure Survey (HIES) (from 2002-3 and 2007-8) as well as the national census of 2007. According to the expenditure based estimates developed in this report, in 2008/09 just over a third of the Fijian population lived in poverty. Poverty in Fiji is driven by multiple factors. The report presents the first national level poverty maps created for Fiji and in the Pacific using the national census, which provides a powerful visual depiction of poverty pockets that can help to ensure that anti-poverty programs reach the poor.